Sanitasi Rumah Kos Mahasiswa di Sekitar Kampus Institut Kesehatan Payung Negeri Pekanbaru - Suryani Suryani; Rahmi Pramulia Fitri S; Sabila Rafa; Dini Astika (Pelantar Press, 2026)
Student boarding houses serve as temporary residences and should comply with adequate sanitation standards to ensure the health and well-being of their occupants. Inadequate sanitation conditions may increase the risk of environment-related diseases and adversely affect students health, comfort, and daily productivity. This study aimed to describe the sanitation conditions of student boarding houses surrounding Institut Kesehatan Payung Negeri Pekanbaru based on housing components, sanitation facilities, and occupants hygiene-related behaviors. A quantitative descriptive design was employed. A total of 76 students were selected through purposive sampling. Data were collected using a Healthy House Assessment Questionnaire and analyzed descriptively using frequency distributions and percentages. The findings revealed that most student boarding houses met the criteria for healthy housing. However, several sanitation deficiencies were identified, including inadequate ventilation, the absence of kitchen smoke exhaust vents, the use of open wastewater drainage systems, and uncovered waste bins. Overall, the sanitation conditions of student boarding houses generally complied with healthy housing standards. Nevertheless, improvements in housing components, sanitation facilities, and occupants hygiene-related behaviors are still required to promote a healthier residental environment for students